Association of inducible nitric oxide synthase with asthma severity, total serum immunoglobulin E and blood eosinophil levels. Issue 1 (23rd August 2006) - Batra, Jyotsna; Pratap Singh, Tej; Mabalirajan, Ulanganathan; Sinha, Aditi; Prasad, Rajendra; Ghosh, Balaram
Abstract : Background: Nitric oxide is released by immune, epithelial and endothelial cells, and plays an important part in the pathophysiology of asthma. Objective: To investigate the association of inducible nitric oxide synthases ( iNOS) gene repeat polymorphisms with asthma. Methods: 230 families with asthma (842 individuals) were recruited to identify and establish the genetic association of iNOS repeats with asthma and associated phenotypes. Serum nitric oxide levels in selected individuals were measured and correlated with specific genotypes. Multiple logistic regression analysis was performed to determine the effect of age and sex. Results: A total of four repeats—a (CCTTT)n promoter repeat, a novel intron 2 (GT)n repeat (BV680047), an intron 4 (GT)n repeat (AFM311ZB1) and an intron 5 (CA)n repeat (D17S1878)—were identified and genotyped. A significant transmission distortion to the probands with asthma was seen for allele 3 of the AFM311ZB1 gene (p = 0.006). This allele was also found to be significantly associated with percentage blood eosinophils (p<0.001) and asthma severity (p = 0.04). Moreover, it was functionally correlated with high serum nitric oxide levels (p = 0.006). Similarly, the promoter repeat was found to be associated with serum total immunoglobulin (Ig)E (p = 0.028). Individuals carrying allele 4 of this repeat have high serum IgE (p<0.001) and nitric oxide levels (p = 0.03). Conclusion: This is the first study to identify the repeat polymorphisms in the iNOS gene that are associated with severity of asthma and eosinophils. The functional relevance of the associated alleles with serum nitric oxide levels was also shown. Therefore, these results could be valuable in elucidating the role of nitric oxide in asthma pathogenesis.